2015
DOI: 10.5173/ceju.2015.582
|View full text |Cite
|
Sign up to set email alerts
|

CyberKnife-based prostate cancer patient radioablation – early results of irradiation in 200 patients

Abstract: IntroductionProstrate cancer (PC) is one of the most common malignancies and is frequently treated with an 8-week course of radiotherapy. CyberKnife (CK) based radioablation enables completion of therapy within 5-9 days. The aim of this study is an evaluation of the effectiveness and tolerance of CyberKnife-based radioablation in prostate cancer patients.Material and methods200 PC patients (94 low risk [LR], 106 intermediate risk [IR]) underwent CK irradiation every other day (fraction dose [fd] 7.25 Gy, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
7
0
1
Order By: Relevance
“…However, some of the resulting optimal plans would have long treatment times or large radiation exposures to the OARs. Long treatment times require patients to lie still for long periods of time, increasing their discomfort and the possibility they will move causing excess radiation to reach normal tissue [ 8 ]. Moreover, allowing long treatment times or excess irradiation to the OARs would conflict with our stated aims, so we did not use an objective function in which all terms were multiplied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some of the resulting optimal plans would have long treatment times or large radiation exposures to the OARs. Long treatment times require patients to lie still for long periods of time, increasing their discomfort and the possibility they will move causing excess radiation to reach normal tissue [ 8 ]. Moreover, allowing long treatment times or excess irradiation to the OARs would conflict with our stated aims, so we did not use an objective function in which all terms were multiplied.…”
Section: Discussionmentioning
confidence: 99%
“…One study has reported that the time for prostate cancer treatment with CyberKnife was about 90 min per session [ 7 ]. However, other researchers have shown mean treatment times of 43 min, excluding the time needed for patient setup [ 6 ], and 40–65 min [ 8 ]. Each of these studies required longer mean treatment times than plans based on possible optimal combinations in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…W badaniu przeprowadzonym przez zespół Miszczyka [6], w którym najdłuższy czas obserwacji wyniósł 26 miesiące, odnotowano stosunkowo niski odsetek działań niepożądanych zastosowanej terapii. Ostre odczyny popromienne ze strony układu moczowego w stopniu 2 według RTOG dotyczyły 8,5%, a w stopniu 3 -1% chorych.…”
Section: Omówienieunclassified
“…This system is used for stereotactic radiosurgery (SRS) and stereotactic body radiotherapy (SBRT) applications. The efficacy of SRS [2,3] and SBRT [4][5][6] applications were demonstrated by large body of literature. In recent years, small field dosimetry gain increased attention and several investigations are going on, to address the issues associated with small fields [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%